The Legal Policy of Corporation Legal Standing as Rechtpersoon at Indonesian Criminal Justice System - . Maryano; . Yuhelson (Postgraduate of Jayabaya University, 2017)
Feature of corporation as activities-oriented for profit can lead to potential violations law or corporate crime. The criminal action corporations can arised because the impact of corporate activities arising from business contracts, product quality problems, failure of information technology systems and negligence of the administrative requirements for business licensing compliance. In other words, the legal entity of crime was often referred as corporate crime as violations committed by businesses to profit more quickly and maintains the company's reputation. The study concluded, first, the political dimension of the criminal law on corporation has general nature, that political criminal law founded in Criminal Code Bill which are oriented to the development of law by placing the corporation as a criminal, and need a codification law of Corporation. Second, The political criminal law also has special nature, which is found in 16 laws examined, in the contexts of criminal responsibility concepts and application of pattern of criminalas well as models of criminal sanctions can be imposed on perpetrators of criminal acts of the corporation.Keywords: Corporate crime of law politics, legal standing, subject crime of law.